IMPOLITENESS COMMENTING ON INSTAGRAM ”KEKEYI” - Emeliya Sukma Dara Damanik; Rora Rizki Wandini (UIN Sumatera Utara, 2020)
This study aims to find the impoliteness strategies in thecommenting of Instagram. The source of the data is takenfrom Instagram account “Kekeyi” a beauty vlogger who viralbecause of her uniqueness “using water balloon as sponge”and her controversy in social media. These situation make herget Bullying from her followers. The harassment and impolitelanguage cannot be avoided in the commenting of Kekeyi’sInstagram. By identifying and analyzing of all the data, thewriter found that there are three strategies of impolitenesslanguage used by the followers. They are bald on record,positive impoliteness and negative impoliteness. Based on thedata, the writer also found that positive impoliteness as thedominant strategy used by her followers. The use of the threestrategies seems as the way of her follower to show theirdisappointment toward what Kekeyi did in her posting andcaption were not what they expected. Studying of languageimpoliteness is very important to avoid verbal bullying insocial media.